The last 25 years of research on bioflocculants for kaolin flocculation with recent trends and technical challenges for the future - Bahniuk, Markian S.; Alidina, Fawad; Tan, Xiaoli; Unsworth, Larry D. (Frontiers in Bioengineering and Biotechnology, 2022)
The generation of Kaolin-containing wastewater is an inevitable consequence in a number of industries including mining, wastewater treatment, and bitumen production. In some cases, the production of Kaolin tailings waste during the production of bitumen or phosphate is as high as 3 times greater than the actual produced product. The existing inventory of nearly five billion barrels of tailings represents a massive storage and reclamation challenge, as well as a significant economic and environmental liability. Current reclamation options like inorganic coagulants and organic synthetic polymers may settle Kaolin effectively, but may themselves pose an additional environmental hazard. Bioflocculants are an emerging alternative, given the inherent safety and biodegradability of their bio-based compositions. This review summarizes effective Kaolin bioflocculants reported in the literature over the last 25 years, with a focus on the bioflocculant source, composition, and effective flocculating conditions. Bacillus bacteria were the most prevalent single species for bioflocculant production, with wastewater also hosting a large number of bioflocculant-producing microorganisms while serving as an inexpensive nutrient. Effective Kaolin flocculation could be obtained over a broad range of pH values (1-12) and temperatures (5-95 °C). Uronic acid and glutamic acid were predominant sugars and amino acids, respectively, in a number of effective bioflocculants, potentially due to their structural and charge similarities to effective synthetic polymers like polyacrylamide. Overall, these results demonstrate that bioflocculants can be produced from a wide range of microorganisms, can be composed of polysaccharides, protein or glycoproteins and can serve as effective treatment options for Kaolin. In some cases, the next obstacle to their wide-spread application is scaling to industrially relevant volumes and their deployment strategies.